2008
DOI: 10.1016/j.ccr.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic-Mediated Dysfunction of the Bone Morphogenetic Protein Pathway Inhibits Differentiation of Glioblastoma-Initiating Cells

Abstract: Despite similarities between tumor-initiating cells with stem-like properties (TICs) and normal neural stem cells, we hypothesized that there may be differences in their differentiation potentials. We now demonstrate that both bone morphogenetic protein (BMP)-mediated and ciliary neurotrophic factor (CNTF)-mediated Jak/STAT-dependent astroglial differentiation is impaired due to EZH2-dependent epigenetic silencing of BMP receptor 1B (BMPR1B) in a subset of glioblastoma TICs. Forced expression of BMPR1B either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
361
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(382 citation statements)
references
References 53 publications
(76 reference statements)
16
361
2
3
Order By: Relevance
“…The results of a recent study (26), similar to our findings, showed that IFN-β induces the phosphorylation of STAT3 in glioma cells and thereby activates STAT3-mediated miR-21 transcription in a luciferase reporter gene system. Our findings support the hypothesis that STAT3 activation exerts a cytostatic or antiproliferative effect in some types of cells (34)(35)(36)(37); however, the role of STAT3 activation is debatable because its overactivation has been reported to be oncogenic in some cell lines (38,39). Loffler et al showed that IL-6-dependent STAT3 activates the transcription of miR-21 in multiple myeloma cells.…”
Section: Discussionsupporting
confidence: 88%
“…The results of a recent study (26), similar to our findings, showed that IFN-β induces the phosphorylation of STAT3 in glioma cells and thereby activates STAT3-mediated miR-21 transcription in a luciferase reporter gene system. Our findings support the hypothesis that STAT3 activation exerts a cytostatic or antiproliferative effect in some types of cells (34)(35)(36)(37); however, the role of STAT3 activation is debatable because its overactivation has been reported to be oncogenic in some cell lines (38,39). Loffler et al showed that IL-6-dependent STAT3 activates the transcription of miR-21 in multiple myeloma cells.…”
Section: Discussionsupporting
confidence: 88%
“…Germ line mutations of BMPR1A have been associated with juvenile polyposis in humans and produce a significantly higher risk of gastrointestinal cancer (33). BMPR1B homozygous null mice are viable; however, mutants exhibit skeletal defects (34), and BMPR1B is epigenetically silenced in some patientderived tumor-initiating glioblastoma cell lines (35). A recent study indicated that lower BMPR1B expression was observed in breast cancer tissues with poor prognosis, and the decreased expression of BMPR1B resulted in increased cell proliferation in breast cancer cells in vitro, which suggested that BMPR1B mediated a repressive effect on breast cancer cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…BMPs were identified based on their ability to promote ectopic cartilage and bone formation (2). BMPs function through conserved type I and type II transmembrane receptors and Smad-dependent and -independent pathways, to regulate a range of biological processes in a highly context-dependent manner (1,(3)(4)(5). Disruption of these pathways can lead to various diseases including cancer (6).…”
Section: Introductionmentioning
confidence: 99%